Nucleotide-Binding Oligomerization Domain-1 and -2 Play No Role in Controlling Brucella abortus Infection in Mice - Fernanda S. Oliveira; Natalia B. Carvalho; Dario S. Zamboni; Sergio C. Oliveira (Clinical and Developmental Immunology)
Nucleotide-binding oligomerization domain proteins (NODs) are modular cytoplasmic proteins implicated in the recognition of peptidoglycan-derived molecules. Further, several in vivo studies have demonstrated a role for Nod1 and Nod2 in host defense against bacterial pathogens. Here, we demonstrated that macrophages from NOD1-, NOD2-, and Rip2-deficient mice produced lower levels of TNF-α following infection with live Brucella abortus compared to wild-type mice. Similar reduction on cytokine synthesis was not observed for IL-12 and IL-6. However, NOD1, NOD2, and Rip2 knockout mice were no more susceptible to infection with virulent B. abortus than wild-type mice. Additionally, spleen cells from NOD1-, NOD2-, and Rip2-deficient mice showed unaltered production of IFN-γ compared to C57BL/6 mice. Taken together, this study demonstrates that NOD1, NOD2 and Rip2 are dispensable for the control of B. abortus during in vivo infection.